SUCCESSFUL EFL TEACHERS IN INDONESIAN EDUCATIONAL CONTEXT: ATTITUDE AND APPROACH - Arkam Arkam (Al-Ishlah: Jurnal Pendidikan Islam, 2015)
This paper explores the notions and issues of Attitude and Approach of EFL teachers in Indonesian Educational Context. The paper was based on some of the findings of a fieldwork conducted in 2014, in which 3 English teachers were interviewed and observed. The aim of the study was to investigate the attitudes of the successful EFL teachers show to the language they are teaching and the teaching styles and methods of the successful EFL teachers consciously develops and employs. Findings from interview data suggest that English teacher should have positive attitudes toward English that they are teaching and also teachers should apply the four language skills and some language elements in form of integrated skills because the skills and the elements connect each other.